The practice of positive psychology coaching. Issue 5 (2nd September 2020) - Biswas-Diener, Robert
ABSTRACT: Coaching facilitates the learning, growth, and performance of clients. This process is a natural fit for positive psychology intervention because of a shared emphasis on positive topics such as optimism, strengths, and motivation. Over the past 15 years in the field, the author's opinions about positive psychology coaching have evolved. This paper outlines his current thinking, highlights how this thinking differs from earlier thoughts and offers practitioners specific issues for consideration. These include (A) creating conditions that will enhance the success of positive psychology interventions in coaching, (B) avoiding prescriptiveness, (C) accessing a wide range of positive psychological science to inform practice, and D) taking an ethical approach to intervention.